(untitled) (Archives of Criminology, 2023)
The aim of this publication is to compare the views of people harmed by the crime of abuse when the perpetrator is ordered to leave the premises with the current legal norms. The research is complemented by opinions from experts (people who support victims of domestic violence professionally). The considerations lead to an attempt at answering the question of whether the legal shape of the order to leave the premises meets the justified needs of the victims.